Diagnosis and Distribution of Florida Sand Darter, Ammocrypta bifascia (Teleostei; Percidae), in the Flint River, Georgia - Camm C Swift; Gregory R. Moyer; Christine E. Fallon; Brett Albanese (Southeastern Fishes Council Proceedings, 2020)
Abstract: In 2013, we observed the presence of an undocumented Ammocrypta species in the lower Flint River, Georgia. The occurrence represents the first record of the genus in Georgia. Subsequent surveys at 24 sites, using seining or snorkeling, documented additional specimens from mainstem sites (n = 3) between Albany and Bainbridge and from Ichawaynochaway Creek (n = 5 sites), a large tributary to the Flint River. We used morphological and genetic data to identify specimens to species. Morphological examination included 23 morphometric and 8 meristic characters from fifteen specimens that were compared to specimens from Williams (1975). For genetic analyses, we targeted the mtDNA cytochrome c oxidase and nuclear ribosomal internal transcribed spacer 2 (ITS-2) genes and compared them to specimens from throughout the geographic range of Ammocrypta. Morphological analyses showed broad overlap in measurements and counts with A. bifascia (Florida Sand Darter). The mtDNA data also grouped our specimens with A. bifascia from the Choctawhatchee River, which is the type locality of A. bifascia. While nuclear data was monomorphic when compared to other A. bifascia, the mtDNA of Flint River A. bifascia shared a unique haplotype that was one or more substitutions apart from other A. bifascia haplotypes. Georgia specimens appear to be native, having a haplotype that is different from other A. bifascia and a distribution pattern that corresponds closely to other fishes. We observed A. bifascia from only a handful of scattered localities in the mainstem of the river and the lower portion of its largest tributary. Past surveys may have failed to detect the species due its limited distribution and the difficulty of collecting small benthic fishes in large river habitats.
Keywords: cryptic biodiversity; Apalachicola drainage; Ichawaynochaway Creek; seining; snorkeling